2020
DOI: 10.1139/cjpp-2019-0413
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota dysbiosis in polycystic ovary syndrome: association with obesity — a preliminary report

Abstract: Objectives: To explore if and how the microbiota changed in PCOS women against healthy women. Methods: Eight obese PCOS (PO group), ten non-obese PCOS (PN group) and nine healthy normal-weight women (control) (C group) were enrolled. Insulin (INS), testosterone (T), follicle-stimulating hormone (FSH), luteinizing hormone (LH), estrogen (E2) and dehydroepiandrosterone (DHEA) were detected with radioimmunoassay. Anti mullerian hormone (AMH), fasting glucose and hemoglobin A1c (HbA1c) were determined by che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…Letrozole treatment of adult mice also resulted in a higher relative abundance of genera from Lachnospiraceae, Ruminococcaceae, and Peptococcaceae, and lower Lactobacillus [52]. In a recent human study, Bacteroidetes, Firmicutes, and Verrucomicrobia phyla differed between women with PCOS and controls, with obesity having a driving role in the development of dysbiotic microbiota [53]. In particular, women with PCOS had higher relative abundances of several Ruminococcus spp.…”
Section: Effects Of Testosteronementioning
confidence: 93%
“…Letrozole treatment of adult mice also resulted in a higher relative abundance of genera from Lachnospiraceae, Ruminococcaceae, and Peptococcaceae, and lower Lactobacillus [52]. In a recent human study, Bacteroidetes, Firmicutes, and Verrucomicrobia phyla differed between women with PCOS and controls, with obesity having a driving role in the development of dysbiotic microbiota [53]. In particular, women with PCOS had higher relative abundances of several Ruminococcus spp.…”
Section: Effects Of Testosteronementioning
confidence: 93%
“…Two groups of beneficial bacteria are dominant in the human gut: Bacteroidetes and Firmicutes (Rinninella et al 2019). Several studies have shown that obesity is related to dysbiosis in the intestinal microbiota in children, adolescents, and adults (Chen, Sun, et al 2020;Jobira et al 2020;Liang et al 2020;Riva et al 2017). Riva et al evidenced an increase and shifts in the phylum Firmicutes and a decrease in Bacteroidetes in fecal samples (Riva et al 2017).…”
Section: The Microbiota Gut-lung Axis and Immune Response In Obesitymentioning
confidence: 99%
“…Of the genera within phylum Bacteroidetes , Bacteroides were positively associated with PCOS in 5/7 studies and Parabacteroides were positively associated with PCOS in 2 studies [ 20 , 23–25 , 28 , 33 ], while the family S24-7 was negatively associated with PCOS in 2 studies [ 19 , 33 ]. Of the genera within phylum Firmicutes , family Clostridiaceae was positively associated with PCOS in 2 studies [ 22 , 25 ] and family Veillonellaceae in 2 other studies [ 27 , 33 ]. Of the genera within phylum Proteobacteria , Escherichia , and Shigella were positively associated with PCOS in 2 studies [ 20 , 22 ].…”
Section: Dysbiosis Of the Gut Microbiome Is Associated With Polycystimentioning
confidence: 99%